2007
DOI: 10.1359/jbmr.070602
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Finger Transcription Factor Odd-Skipped Related 2 Is One of the Regulators in Osteoblast Proliferation and Bone Formation

Abstract: We report that Osr2 is one of the regulators of osteoblast function, because dominant-negative Osr2 transgenic mice exhibited decreased osteoblast activity and delayed mineralization in calvarial and tibial bone tissues. Our results indicate that Osr2 functions in regulation of osteoblast proliferation.Introduction: Molecular mechanisms that control bone formation have received attention with increasing knowledge related to genetic control of osteoblast differentiation. The odd-skipped related (Osr) gene is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…Although the specific Osr1-binding DNA sequence has not been reported, a previous PCR-based DNA-binding sequence selection study suggested that the mouse Osr2 protein binds to a core DNA sequence similar to that bound by the Drosophila odd-skipped protein (36,37). Osr1 and Osr2 share almost identical DNA-binding domains (11).…”
Section: Aberrant Cartilage Formation In the Tongue In Mice With Neuralmentioning
confidence: 99%
“…Although the specific Osr1-binding DNA sequence has not been reported, a previous PCR-based DNA-binding sequence selection study suggested that the mouse Osr2 protein binds to a core DNA sequence similar to that bound by the Drosophila odd-skipped protein (36,37). Osr1 and Osr2 share almost identical DNA-binding domains (11).…”
Section: Aberrant Cartilage Formation In the Tongue In Mice With Neuralmentioning
confidence: 99%
“…Alkaline phosphatase, collagenase, and aminoacyl-tRNA synthetase are some of the zinc-dependent enzymes, which can impact bone metabolism and are likely to be affected by imbalanced zinc levels [64,315,318]. Gli-similar 3 (Glis3) and Odd-skipped related 2 (Osr2) are zinc finger transcription factors that promote osteoblast differentiation [319,320]. Zinc may also affect several aspects of osteoblast differentiation, presumably by modulating gene expression of runtrelated transcription factor 2 (Runx2) [321,322].…”
Section: Zincmentioning
confidence: 99%
“…Analysis of mutant lines has indicated that these genes are required for proper formation and/or patterning of the endoderm, the heart, the teeth, the palate, the bones and the synovial joints in the limbs (Gao et al, 2011;Kawai et al, 2007;Lan et al, 2004;Mudumana et al, 2008;Wang et al, 2005;Zhang et al, 2009). Expression studies in mice and chicken indicate that, in the limb, Osr genes are expressed from very early stages in a highly dynamic pattern (Lan et al, 2001;So and Danielian, 1999;Stricker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%